The Institutionalisation of Evaluation in Europe
XXIV, 522 p. 19 illus., 5 illus. in color.
Keywords: This book examines the progress of institutionalisation of evaluation in European countries from various perspectives. . It describes both prior developments and current states of evaluation in 16 European countries and across the European Union (EU), focussing on three dimensions, namely the political, social and professional systems. These detailed country reports, which have been written by selected researchers and authors from each of the respective countries, lead to a concluding comparison and synthesis. This is the first of four volumes of the compendium The Institutionalisation of Evaluation to be followed by volumes on the Americas, Africa and Australasia. The overall aim is to provide an interdisciplinary audience with cross-country learning to enable them to better understand the institutionalisation of evaluation in different nations, world regions and different sectors. Reinhard Stockmann is Professor for Sociology at Saarland University, Germany.He is Founder and Director of the Center for Evaluation (CEval), Managing Director of two Master of Evaluation programs, Executive Editor of the German Journal of Evaluation (ZfEv) and Founding member of the German Society for Evaluation (DeGEval). He is an evaluation specialist in the field of development cooperation, education, vocational training, environmental policy and foreign cultural policy. Wolfgang Meyer is Assistant Professor at Saarland University, Germany and Adjunct Professor at Uganda Technology and Management University, Kampala, Uganda. He is Vice-Director of the Centre for Evaluation (CEval), Founding Member of the German Evaluation Society (DeGEval), Sociologist with a Focus on Empirical Methodology and Evaluation Specialist in the Field of Environment, Labour Market and Regional Development. Lena Taube was previously a research associate at the Center for Evaluation (CEval) at Saarland University, Germany, where she focused on research regarding the institutionalisation of evaluation as a means to good governance. She is currently working at the German Institute for Development Evaluation (DEval) engaged with evaluating human rights in German development aid.